Cost‐benefit trade‐offs in acquirers' goodwill valuations - Koonce, Lisa; Toynbee, Sara; White, Brian J. (Contemporary Accounting Research, 2025)
Abstract Academic and anecdotal evidence suggests that acquirers prefer to record higher goodwill values in business combinations so they can benefit from higher post‐acquisition earnings when goodwill is only tested for impairment. We conduct multiple experiments to test the hypothesis that this perspective ignores two costs that acquirers may also consider. Specifically, goodwill generally carries negative market perceptions and is associated with a risk of costly future impairment losses. Our results indicate that consideration of these two costs offsets acquirers' preferences for the earnings benefit of upwardly biasing goodwill. We also document that when there is no earnings benefit from higher goodwill valuations—namely, in a setting where goodwill is amortized to expense—we observe acquirers downwardly biasing goodwill values. Overall, our findings add nuance to our understanding of managerial discretion in the context of business combinations.